Diffuse alveolar hemorrhage in childhood-onset systemic lupus erythematosus: a severe disease flare with serious outcome - Blay, Gabriela (2018)
OBJECTIVE: To evaluate prevalence, clinical manifestations, laboratory abnormalities and treatment in a multicenter cohort study including 847 childhood-onset systemic lupus erythematosus (cSLE) patients with and without diffuse alveolar hemorrhage (DAH), as well as concomitant parameters of severity. METHODS: DAH was defined as the presence of at least three respiratory symptoms/signs associated with diffuse interstitial/alveolar infiltrates on chest x-ray or high-resolution computer tomography and sudden drop in hemoglobin levels. Statistical analysis was performed using Bonferroni correction (p < 0.0022). RESULTS: DAH was observed in 19/847 (2.2%) cSLE patients. Cough/dyspnea/tachycardia/hypoxemia occurred in all cSLE patients with DAH. Concomitant parameters of severity observed were: mechanical ventilation in 14/19 (74%), hemoptysis 12/19 (63%), macrophage activation syndrome 2/19 (10%) and death 9/19 (47%). Further analysis of cSLE patients at DAH diagnosis compared to 76 cSLE control patients without DAH with same disease duration [3 (1-151) vs. 4 (1-151) months, p = 0.335], showed higher frequencies of constitutional involvement (74% vs. 10%, p < 0.0001), serositis (63% vs. 6%, p < 0.0001) and sepsis (53% vs. 9%, p < 0.0001) in the DAH group. The median of disease activity score(SLEDAI-2 K) was significantly higher in cSLE patients with DAH [18 (5-40) vs. 6 (0-44), p < 0.0001]. The frequencies of thrombocytopenia (53% vs. 12%, p < 0.0001), intravenous methylprednisolone (95% vs. 16%, p < 0.0001) and intravenous cyclophosphamide (47% vs. 8%, p < 0.0001) were also significantly higher in DAH patients. CONCLUSIONS: This was the first study to demonstrate that DAH, although not a disease activity score descriptor, occurred in the context of significant moderate/severe cSLE flare. Importantly, we identified that this condition was associated with serious disease flare complicated by sepsis with high mortality rate.